Social media as a workplace panopticon: The development and validation of social media monitoring by workplace contacts scale. - Hamnah Rahat; Sadia Nadeem (PLoS ONE)
The monitoring of employees' private social network accounts by employers and colleagues has become increasingly prevalent, yet research in this area remains limited. To address this gap, the present study developed and validated a scale to measure social media monitoring by workplace contacts (SMMWC). The scale, comprising fifteen items, was developed using Hinkin's (1998) approach to scale development and has four dimensions based on the concept of panoptic effect by Foucault (1977) and Botan (1996). While Study 1, based on 334 employees, focused on scale development, Study 2, based on 302 employees, replicated the factor structure of the SMMWC scale and examined its impact on outcomes, using a time-lagged design. The SMMWC scale demonstrated strong psychometric properties, including factorial validity; discriminant validity with electronic performance monitoring and user perceptions of social media monitoring; and criterion-related validity with online disclosure, social capital, emotional exhaustion, and self-concept clarity. Notably, SMMWC was positively associated with online disclosure in both the studies and was significantly related to emotional exhaustion and self-concept clarity in Study 2, suggesting that SMMWC can influence employees' online behavior and psychological well-being.